What are the clinical and quality of life outcomes for patients 5 years after coronary artery bypass grafting surgery? : A Systematic Review - Nizar Fathurrohman; Hari Agung Asari (International Medical Journal Corp. Ltd, 2025)
Introduction: Coronary Artery Bypass Grafting (CABG) is a crucial surgical intervention for complex coronary artery disease, with well-documented long-term clinical effectiveness. However, a significant gap exists in the literature regarding patient-centered outcomes, particularly long-term quality of life (QoL), which is inconsistently measured. This systematic review aims to comprehensively evaluate both the clinical and QoL outcomes for patients five years after undergoing CABG surgery. Methods: This review adhered to the PRISMA 2020 guidelines. A systematic search was conducted across multiple databases, including PubMed, Springer, Google Scholar, Semantic Scholar, and Wiley Online Library, using predefined inclusion criteria. Studies were required to have a minimum follow-up of five years and report on clinical outcomes or validated QoL measures. A total of 25 studies met the eligibility criteria for the final synthesis. Results: The synthesized data revealed robust clinical effectiveness, with five-year all-cause mortality rates ranging from 8.4% to 23.6% and Major Adverse Cardiac and Cerebrovascular Events (MACCE) rates between 22.6% and 31%. The use of arterial grafts and participation in cardiac rehabilitation were consistently associated with improved outcomes. In stark contrast, only two of the 25 included studies systematically measured QoL using validated instruments, highlighting a significant evidence gap. Discussion: While the clinical durability of CABG is well-established, the systemic failure to report on long-term QoL limits a holistic understanding of patient recovery. Key determinants of long-term success include strategic factors like arterial graft selection and diligent postoperative care, rather than the choice between on-pump and off-pump techniques. High-risk populations, including women and patients with anemia, were identified as having worse outcomes. Conclusion: CABG provides excellent and durable five-year clinical outcomes, particularly when arterial grafts and cardiac rehabilitation are utilized. However, there is an urgent need for future research to integrate standardized QoL metrics as primary endpoints. Shifting the focus from mere survival to ensuring patients thrive is essential for advancing patient-centered care in cardiac surgery.